2021
DOI: 10.1111/ijac.13879
|View full text |Cite
|
Sign up to set email alerts
|

MWCNT/Ti‐doped ZnO nanocomposite as electrochemical sensor for detecting glutamate and ascorbic acid

Abstract: Attributed to high stability and reproducibility, non-enzymatic electrochemical sensors have been extensively utilized in detection of various chemical substances. In this study, multi-walled carbon nanotube (MWCNT)/Ti-doped ZnO composite was prepared for fabrication of working electrode used in detection of glutamate and ascorbic acid. Ti-doped ZnO particles with the average size of 44.47 ± 4.05 nanometers were synthesized by the solution combustion technique. Hydrothermal impregnation was employed in prepara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previously, the solution combustion method has been applied in the synthesis of zinc oxide for the electrochemical detection of dopamine [58]. In addition, multiwalled carbon nanotubes (MWCNTs)/Ti-doped ZnO composites have been synthesized via the solution combustion method followed by hydrothermal impregnation [59]. The gas sensing performance of selfassembled porous ZnO/In 2 O 3 heterostructures through the solution combustion method has been examined towards Cl 2 and other hazardous gases detection [60].…”
Section: Combustion Routementioning
confidence: 99%
“…Previously, the solution combustion method has been applied in the synthesis of zinc oxide for the electrochemical detection of dopamine [58]. In addition, multiwalled carbon nanotubes (MWCNTs)/Ti-doped ZnO composites have been synthesized via the solution combustion method followed by hydrothermal impregnation [59]. The gas sensing performance of selfassembled porous ZnO/In 2 O 3 heterostructures through the solution combustion method has been examined towards Cl 2 and other hazardous gases detection [60].…”
Section: Combustion Routementioning
confidence: 99%
“…Disappointingly, despite the complicated and costly synthesis process of the precisely structured nanowire, the sensitivity and linear range of detection were far removed from expectations. Since then, even though the non-enzymatic glutamate sensors have been developed for ten years, there are still a limited number of works of literature published [18][19][20][21][22][23]. Islam et al reported RuO 2 -doped ZnO nanoparticles based on a non-enzymatic glutamate sensor, which reports a high sensitivity of up to 9.6 × 10 −5 µA/mM•cm 2 and the lowest detection limit of 0.0001 µM [22].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high-efficient sensing analysis, the performance of MOSs can be further improved by surface modification, doping and heterostructures construction. For example, ZnObased composites, like MWCNT/Ti-doped ZnO, [21] ZnO/rGO, [22] ZnO/polypyrrole, [23] ZnO/gÀ C 3 N 4 , [24] and NiOÀ ZnO, [25] show enhanced sensing property. Particularly, ZnO has photocatalytic function and widely application.…”
Section: Introductionmentioning
confidence: 99%